ANALISIS INFLUENCER MARKETING, ONLINE CUSTOMER REVIEW, DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN ONLINE GEN MILENIAL - Wiyarno Wiyarno; Indra Permana; Erna Apriani (JURNAL LENTERA BISNIS, 2025)
In this digital age digital age, online shopping transactions have become a habit that has become ubiquitous It has mushroomed everywhere even almost all circles. Various generations are in fact already so familiar with online shopping transactions, not just shopping, but also selling online. shopping, but the way of selling has also been dominated by online. Changes and technological developments have become one of the strong factors in changes in online behavior at this time, so that the online behavior at this time, so that technological sophistication makes online purchasing decisions very necessary to be analyzed more deeply. online purchasing decisions need to be analyzed more deeply. No wonder if the development of digitalization in influencing human behavior is so fast, because by only transacting online we don't need to leave the house, save time, and can transact online. time, and can transact virtually, and buy and sell online. Basically the purpose of the research conducted to analyze the factors that influencing online purchasing decisions especially millennial genes, namely influencer marketing, online customer review, and digital marketing. marketing, online customer reviews, and digital marketing. Type of research is quantitative research with the research sample being gen millennial students of Pelita Bangsa University who have made online shopping transactions with a purposive sampling of 100 respondents. shopping online with purposive sampling 100 respondents. Data analysis technique using SEM (Stuctural Equation Modeling). The results of this study indicate that the influencer marketing variable does not affect the millennial gen online purchasing decision, then the online customer review variable does not affect the millennial gen online purchasing decision, but the digital marketing variable affects the millennial gen online purchasing decision